2008
DOI: 10.1529/biophysj.107.124024
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Streptavidin Protein Coats on Phase-Separating Model Membranes

Abstract: Heterogeneities in cell membranes due to the ordering of lipids and proteins are thought to play an important role in enabling protein and lipid trafficking throughout the secretory pathway and in maintaining cell polarization. Protein-coated vesicles provide a major mechanism for intracellular transport of select cargo, which may be sorted into lipid microdomains; however, the mechanisms and physical constraints for lipid sorting by protein coats are relatively unexplored. We studied the influence of membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…S4). The tetravalent binding of streptavidin to DPPEbiotin yielded no apparent variations in the membrane topography as assessed with pPLM at any of the streptavidin or DPPE-biotin concentrations tested, consistent with previous reports (26). Taken together, these findings support the hypothesis that the spatial organization of GM1 binding sites in CTxB is important for the curvature generation process.…”
Section: Spatial Organization Of Gm1 Binding Is Necessary For Inducinsupporting
confidence: 91%
“…S4). The tetravalent binding of streptavidin to DPPEbiotin yielded no apparent variations in the membrane topography as assessed with pPLM at any of the streptavidin or DPPE-biotin concentrations tested, consistent with previous reports (26). Taken together, these findings support the hypothesis that the spatial organization of GM1 binding sites in CTxB is important for the curvature generation process.…”
Section: Spatial Organization Of Gm1 Binding Is Necessary For Inducinsupporting
confidence: 91%
“…This work is consistent with earlier studies in suggesting that lipid-mediated membrane heterogeneity can be stabilized by controlling the localization of a subset of components. Previous work in model membranes with coexisting L o and L d phases have shown that lipid heterogeneity is stabi-lized when lipids are tethered to cross-linked actin meshworks (39) or to 2D crystals of avidin (40). In both cases, experimental results of probe partitioning into or away from protein-coated membrane domains was interpreted as an increase in transition temperature.…”
Section: Discussionmentioning
confidence: 99%
“…By using streptavidin-coated surfaces, individual biotinylated vesicles can be immobilized on surfaces for imaging [116,117]. The presence of the surface may affect the free energy of the system [118], but the ability to make extended observations of a single virus-liposome complex provides an approach that can overcome the limitations of bulk fusion assays due to the stochastic nature of each fusion event and the difficulty in synchronizing fusion of large ensembles of particles. Liposome targets also allow the role of membrane curvature to be tested in fusion experiments.…”
Section: Experimental Techniques That Reveal Dynamics Of Membrane Fusionmentioning
confidence: 99%